CORPORATE SOCIAL RESPONSIBILITY AND BUSINESS REPUTATION OF COMMERCIAL BANKS IN NIGERIA - Thomas C. OKOISAMA; Godwin I. UMOH; Hubert D. HETTEY; Patrick O. ISHIE (Scholars Digest Publishing, 2025)
The study investigated the relationship between corporate social responsibility (dimensioned by developmental responsibilities, ethical responsibility, and environmental impact reduction) and the business reputation of commercial banks in Nigeria.
Keywords: Corporate Social Responsibility, Business Reputation, Commercial Banks.